Ambulatory Surgical Services Provided Under California Workersâ€™ Compensation - Barbara O. Wynn, John P. Caloyeras, and Nelson F. Soohoo (RAND Corporation, 2014)
Californiaâ€™s Official Medical Fee Schedule (OMFS) establishes the maximum allowable fee for medical services provided under the stateâ€™s workers compensation program unless the payer and provider contract for a different payment amount. The OMFS allows facility fees for surgical services performed in an ambulatory surgical center. The allowances are based on the Medicare fee schedule for hospital outpatient services, which includes only services that the Centers for Medicare & Medicaid Services has determined can be safely performed in the outpatient setting on Medicare beneficiaries. It excludes services that Medicare has decided can only be performed on an inpatient basis, such as multi-level spinal fusions, and hip and knee replacements. California Senate Bill 863 requires that the Department of Industrial Relations study the feasibility of establishing facility fees for Medicareâ€™s â€œinpatient onlyâ€ procedures when they are performed on workersâ€™ compensation patients in an ambulatory surgical center and report the study findings to the Senate Labor Committee and Assembly Insurance Committee. The Department asked RAND to examine the feasibility and appropriateness of including Medicareâ€™s â€œinpatient onlyâ€ procedures on the OMFS.